LEVELS OF HEAVY METAL IN THE FILLET, GILLS AND LIVER OF Clarias gariepinus and Parauchenoglanis fasciatus in AHO STREAM, ILE-IFE - KOMOLAFE, O. O.; ADEBISI, R. A.; LAWAL, O. A. (Nigerian Journal of Fisheries, 2013)
Fishes are a good source of protein and are useful in evaluating the status of water pollution especially in the fresh water ecosystem. Cadmium, chromium, nickel and zinc levels in the fillet, gills and liver of Clarias gariepinus and Parauchenoglanis sp were assayed. Result showed that cadmium values ranged between 0.001 ppm-0.022 ppm, chromium ranged between 0.001 ppm - 0.010 ppm, nickel was found within the range 0.001 ppm - 0.011 ppm while zinc ranged between 0.001 ppm - 0.016 ppm. The concentration of chromium, zinc, copper and nickel in the fillet, gills and liver of the two fish species were low and within internationally accepted limit. Hence, fish species of Aho stream can be considered safe for human consumption.